Quality-by-design approach for the development of telmisartan potassium tablets - Oh, Ga Hui; Park, Jin Hyun; Shin, Hye Won; Kim, Joo Eun; Park, Young Joon (Drug Development and Industrial Pharmacy, 2018)
A quality-by-design approach was adopted to develop telmisartan potassium (TP) tablets, which were bioequivalent with the commercially available Micardis® (telmisartan free base) tablets. The dissolution pattern and impurity profile of TP tablets differed from those of Micardis® tablets because telmisartan free base is poorly soluble in water. After identifying the quality target product profile and critical quality attributes (CQAs), drug dissolution, and impurities were predicted to be risky CQAs. To determine the exact range and cause of risks, we used the risk assessment (RA) tools, preliminary hazard analysis and failure mode and effect analysis to determine the parameters affecting drug dissolution, impurities, and formulation. The range of the design space was optimized using the face-centered central composite design among the design of experiment (DOE) methods. The binder, disintegrant, and kneading time in the wet granulation were identified as X values affecting Y values (disintegration, hardness, friability, dissolution, and impurities). After determining the design space with the desired Y values, the TP tablets were formulated and their dissolution pattern was compared with that of the reference tablet. The selected TP tablet formulated using design space showed a similar dissolution to that of Micardis® tablets at pH 7.5. The QbD approach TP tablet was bioequivalent to Micardis® tablets in beagle dogs.
Keywords: Animals; Benzimidazoles; Benzoates; Dogs; Drug Compounding; Drug Liberation; Excipients; Potassium; Tablets; bioequivalence; design of experiment; design space; quality-by-design; risk assessment; Telmisartan potassium